Iron phthalocyanine and cobalt nickel hydroxide layered material compounded bifunctional catalyst as well as preparation method and application thereof

Through ultrasonic-assisted room temperature precipitation method, the composite iron phthalocyanine and cobalt nickel layered double hydroxides solved the problem of poor catalytic performance and stability of composite materials in the prior art, and the improvement and catalytic activity of oxygen reduction and oxygen precipitation are achieved. Extended lifespan, low cost and environmentally friendly.

CN119170809AActive Publication Date: 2024-12-20ANHUI UNIVERSITY OF TECHNOLOGY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411234996.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2024-12-20
Estimated Expiration
2044-09-04

AI Technical Summary

Technical Problem

The prior art is difficult to effectively recombinate iron phthalocyanine and layered bimetallic hydroxide, resulting in poor catalytic performance and stability, and is unable to effectively improve the bidirectional catalytic activity of oxygen reduction and oxygen precipitation.

Method used

By using a one-step ultrasonic assisted room temperature precipitation method, iron phthalocyanine is combined with cobalt-nickel layered double hydroxide, by uniformly dispersing the cobalt salt and nickel salt in an organic solvent, iron phthalocyanine powder is added and precipitated in a strong alkali solution. Form a tight composite material.

Benefits of technology

It improves the bidirectional catalytic performance of oxygen reduction and oxygen precipitation, extends the catalytic life, is simple in material preparation technology, is low in cost, is green and environmentally friendly, and has excellent electrocatalytic performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170809A_ABST
    Figure CN119170809A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of energy materials and electrochemistry, in particular to an iron phthalocyanine and cobalt nickel hydroxide layered material compounded bifunctional catalyst and a preparation method and application thereof.According to the method, iron phthalocyanine (FePc), cobalt salt and nickel salt serve as metal sources, an ultrasonic-assisted strong base precipitation method is adopted, and the composite catalyst is prepared in situ at the room temperature in one step. The method is simple in preparation process, mild in synthesis condition, wide in raw material source and low in cost. Under the alkaline condition, the composite catalyst is excellent in electro-catalytic performance and has a relatively great application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of energy materials and electrochemical technology, and in particular to a bifunctional catalyst composited with iron phthalocyanine and cobalt nickel hydroxide layered materials, a preparation method and application thereof. Background Art

[0002] The rapid depletion of fossil energy has brought about serious environmental problems and energy shortages, which has promoted the research of a series of green energy conversion and storage technologies. Compared with other batteries, zinc-air batteries have obvious advantages such as low cost, environmental friendliness, long charge and discharge life, and high safety. However, the battery performance is still unsatisfactory due to the sluggish kinetics of the oxygen reduction reaction (ORR) during discharge and the oxygen evolution reaction (OER) during charging of the air electrode. In order to overcome the obstacles of these two reactions, high-performance ORR and OER catalysts are required. At present, the precious metal Pt is considered to be the most effective ORR catalyst, but the OER activity is poor, while the precious metals Ir and Ru are excellent OER catalysts, but the ORR activity is poor and can only play a single catalytic role. More importantly, precious metal catalysts also have disadvantages such as high cost and poor stability. Therefore, the rational design of cost-effective, highly active, and highly stable bifunctional ORR / OER electrocatalysts is crucial for the practical application of zinc-air batteries.

[0003] At present, researchers have developed many materials as bifunctional oxygen electrode catalysts, such as heteroatom-doped carbon nanomaterials, transition metal compounds, etc. Among them, iron phthalocyanine (FePc) materials with N-coordinated iron single atoms are considered to be one of the most effective non-precious metal ORR catalysts, but their OER catalytic performance is not ideal. For OER, transition metal (hydr)oxides are one of the most promising non-precious metal catalysts, especially layered double hydroxides (LDHs) with a layered structure. Effectively combining the two materials is a feasible means to synergistically improve the ORR / OER catalytic activity. LDH and FePc composites are often directly mixed with LDH and commercial iron phthalocyanine by means of mechanical ball milling, because commercial FePc particles are large and have uneven morphology. At the same time, FePc particles and LDH nanosheets are in point-to-point contact, the combination of the two is poor, and the catalytic performance and stability of the composite material are poor. Therefore, it is necessary to find a suitable method to obtain high-performance LDH and FePc composites.

[0004] Chinese invention patent CN202010758587.8 discloses a method for preparing and applying a heterostructured iron / cobalt bimetallic phthalocyanine electrocatalyst, and the preparation method includes: using a solvent thermal method to phase-transform the bimetallic phthalocyanine to composite the bimetallic phthalocyanine. Chinese invention patent application CN202310766027.0 discloses a method for preparing a metal sulfide composite bifunctional electrocatalyst and its application. The preparation method of the metal sulfide composite material includes: dissolving graphene oxide, a cobalt source, a nickel source, and a sulfur source and then hydrothermally obtaining a metal sulfide composite material. The application scenarios of the above technical solutions are all zinc-air batteries. It should be pointed out that both of the above technical solutions require the use of a solvent thermal method, which has high energy consumption and the particle size of the crystallized composite material is not easy to control. Summary of the invention

[0005] The purpose of the present invention is to solve the problem of how to effectively compound two materials to obtain a layered double hydroxide (LDHs) with a layered structure, thereby synergistically improving the ORR / OER catalytic activity. A bifunctional catalyst composite of iron phthalocyanine and cobalt nickel hydroxide layered materials, a preparation method and its application are provided.

[0006] In order to achieve the above object, the present invention discloses a method for preparing a bifunctional catalyst composited with iron phthalocyanine and cobalt nickel hydroxide layered materials, comprising the following steps:

[0007] S1, uniformly dispersing cobalt salt and nickel salt in an organic solvent to obtain a dispersion;

[0008] S2, slowly adding iron phthalocyanine powder to the dispersion in step S1, and ultrasonicating for 0.1 to 60 hours;

[0009] S3, quickly injecting the dispersion obtained after ultrasonic treatment in step S2 into the strong alkaline solution, injecting 100 to 1000 μL each time until the dispersion is completely injected to obtain a mixed solution;

[0010] S4, subjecting the mixed solution obtained in step S3 to ultrasonic treatment for 0.1 to 80 hours, washing, centrifuging and drying after the ultrasonic treatment to obtain a bifunctional catalyst composed of iron phthalocyanine and cobalt nickel hydroxide layered material, recorded as FePc-LDH.

[0011] In step S1, the cobalt salt is any one of cobalt chloride, cobalt nitrate, and cobalt sulfate, or a mixture of two or more thereof; the nickel salt is any one of nickel chloride, nickel nitrate, and nickel sulfate, or a mixture of two or more thereof; and the organic solvent is any one of methanol, ethanol, and N,N-dimethylformamide, or a mixture of two or more thereof.

[0012] In the step S1, the molar ratio of the cobalt salt to the nickel salt is 3:2.

[0013] In the step S2, the dispersion amount of iron phthalocyanine is 2 to 200 mg / mL.

[0014] In step S3, the strong alkaline solution is any one of lithium hydroxide, sodium hydroxide, and potassium hydroxide, or a mixture of two or more thereof.

[0015] In step S3, the molar concentration of the strong alkaline solution is 0.1-10 mol / L.

[0016] In step S4, the solvent used for washing is any one of acetone, ethanol, and deionized water, or a mixture of two or more thereof.

[0017] In step S4, the drying is carried out by any one of ordinary air oven drying, vacuum drying, freeze drying or a mixture of two or more thereof, and the drying time is 1 to 144 hours.

[0018] The invention also discloses a dual-function catalyst composited with iron phthalocyanine and cobalt nickel hydroxide layered material prepared by the preparation method.

[0019] Compared with the prior art, the beneficial effect of the present invention is that the present invention uses a one-step ultrasound-assisted room temperature precipitation method to compound iron phthalocyanine and cobalt-nickel layered double hydroxide. This composite design promotes the synergistic effect between iron, cobalt and nickel metals, increases the tightness of the combination of the two materials, effectively improves the bidirectional catalytic performance of oxygen reduction and oxygen evolution, and prolongs the catalytic life. The material preparation process is simple, the synthesis conditions are mild, the raw material source is wide, the cost is low, it is green and environmentally friendly, and the repetition rate is high. The composite catalyst has excellent electrocatalytic performance and has great application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 TEM image of the iron phthalocyanine and cobalt nickel layered double hydroxide composite material prepared in Example 1;

[0021] Figure 2 X-ray diffraction patterns of the materials prepared in Example 1 and Comparative Example 1;

[0022] Figure 3 The Fourier transform infrared spectra of the composite materials prepared in Example 1, Comparative Example 1 and Comparative Example 2;

[0023] Figure 4 The linear sweep voltammetry (LSV) curves of OER of the composite materials prepared in Example 1, Comparative Example 1 and Comparative Example 2 under 1 M KOH conditions;

[0024] Figure 5 The linear sweep voltammetry (LSV) curves of ORR of the composite materials prepared in Example 1, Comparative Example 1 and Comparative Example 2 under 0.1 M KOH conditions are shown.

[0025] Figure 6 The linear sweep voltammetry (LSV) curves of OER of the composite materials prepared in Example 1, Example 2 and Example 3 under 1 M KOH conditions;

[0026] Figure 7 The linear sweep voltammetry (LSV) curves of ORR of the composite materials prepared in Example 1, Example 2 and Example 3 under 0.1 M KOH conditions are shown.

[0027] Figure 8 The linear sweep voltammetry (LSV) curves of OER of the composite materials prepared in Example 1, Example 4 and Example 5 under 1 M KOH conditions;

[0028] Fig. 9 The linear sweep voltammetry (LSV) curves of ORR of the composite materials prepared in Example 1, Example 4 and Example 5 under 0.1 M KOH conditions are shown. DETAILED DESCRIPTION

[0029] The above and other technical features and advantages of the present invention are described in more detail below in conjunction with the accompanying drawings.

[0030] Example 1

[0031] A bifunctional catalyst composited with iron phthalocyanine and cobalt nickel hydroxide layered materials and a preparation method thereof, comprising the following steps:

[0032] (1) Disperse 3 mmol of cobalt nitrate and 2 mmol of nickel nitrate evenly in 10 mL of anhydrous ethanol.

[0033] (2) Slowly add 200 mg of iron phthalocyanine powder into the dispersion and sonicate for 1 h.

[0034] (3) The dispersion obtained by ultrasound was quickly injected into 20 mL of 1 M KOH, 50 μL at a time, until it was completely injected.

[0035] (4) The resulting mixed solution was sonicated for 1 hour, and after the sonication was completed, it was washed, centrifuged, and dried to obtain a bifunctional catalyst composed of iron phthalocyanine and cobalt nickel hydroxide layered material, which was recorded as FePc-LDH.

[0036] Example 2

[0037] A bifunctional catalyst composited with iron phthalocyanine and cobalt nickel hydroxide layered materials and a preparation method thereof, comprising the following steps:

[0038] (1) Disperse 3 mmol of cobalt nitrate and 2 mmol of nickel nitrate evenly in 10 mL of anhydrous ethanol.

[0039] (2) Slowly add 2 mg of iron phthalocyanine powder into the dispersion and sonicate for 1 h.

[0040] (3) The dispersion obtained by ultrasound was quickly injected into 20 mL of 1 M KOH, 50 μL at a time, until it was completely injected.

[0041] (4) The resulting mixed solution was sonicated for 1 hour, and after the sonication was completed, it was washed, centrifuged, and dried to obtain a bifunctional catalyst composed of iron phthalocyanine and cobalt nickel hydroxide layered material, which was recorded as FePc-LDH-2.

[0042] Example 3

[0043] A bifunctional catalyst composited with iron phthalocyanine and cobalt nickel hydroxide layered materials and a preparation method thereof, comprising the following steps:

[0044] (1) Disperse 3 mmol of cobalt nitrate and 2 mmol of nickel nitrate evenly in 10 mL of anhydrous ethanol.

[0045] (2) Slowly add 20 mg of iron phthalocyanine powder into the dispersion and sonicate for 1 h.

[0046] (3) The dispersion obtained by ultrasound was quickly injected into 20 mL of 1 M KOH, 50 μL at a time, until it was completely injected.

[0047] (4) The resulting mixed solution was sonicated for 1 hour, and after the sonication was completed, it was washed, centrifuged, and dried to obtain a bifunctional catalyst composed of iron phthalocyanine and cobalt nickel hydroxide layered material, which was recorded as FePc-LDH-3.

[0048] Example 4

[0049] A bifunctional catalyst composited with iron phthalocyanine and cobalt nickel hydroxide layered materials and a preparation method thereof, comprising the following steps:

[0050] (1) Disperse 3 mmol of cobalt nitrate and 2 mmol of nickel nitrate evenly in 10 mL of anhydrous ethanol.

[0051] (2) Slowly add 200 mg of iron phthalocyanine powder into the dispersion and sonicate for 0.5 h.

[0052] (3) The dispersion obtained by ultrasound was quickly injected into 20 mL of 1 M KOH, 50 μL at a time, until it was completely injected.

[0053] (4) The resulting mixed solution was sonicated for 1 hour, and after the sonication was completed, it was washed, centrifuged, and dried to obtain a bifunctional catalyst composed of iron phthalocyanine and cobalt nickel hydroxide layered material, which was recorded as FePc-LDH-0.5h.

[0054] Example 5

[0055] A bifunctional catalyst composited with iron phthalocyanine and cobalt nickel hydroxide layered materials and a preparation method thereof, comprising the following steps:

[0056] (1) Disperse 3 mmol of cobalt nitrate and 2 mmol of nickel nitrate evenly in 10 mL of anhydrous ethanol.

[0057] (2) Slowly add 200 mg of iron phthalocyanine powder into the dispersion and sonicate for 6 h.

[0058] (3) The dispersion obtained by ultrasound was quickly injected into 20 mL of 1 M KOH, 50 μL at a time, until it was completely injected.

[0059] (4) The resulting mixed solution was sonicated for 1 hour, and after the sonication was completed, it was washed, centrifuged, and dried to obtain a bifunctional catalyst composed of iron phthalocyanine and cobalt nickel hydroxide layered material, which was recorded as FePc-LDH-6h.

[0060] Comparative Example 1

[0061] A cobalt-nickel hydroxide layered material catalyst and a preparation method thereof, comprising the following steps:

[0062] (1) Disperse 3 mmol of cobalt nitrate and 2 mmol of nickel nitrate evenly in 10 mL of anhydrous ethanol.

[0063] (2) The dispersion obtained by ultrasound was quickly injected into 20 mL of 1 M KOH, 50 μL at a time, until it was completely injected.

[0064] (3) The resulting mixed solution was sonicated for 1 h, and after the sonication was completed, it was washed, centrifuged, and dried to obtain a bifunctional catalyst based on cobalt nickel hydroxide layered material, recorded as CoNi-LDH.

[0065] Comparative Example 2

[0066] A catalyst based on iron phthalocyanine and a preparation method thereof, comprising the following steps:

[0067] (1) Disperse 200 mg of iron phthalocyanine powder evenly in 10 mL of anhydrous ethanol.

[0068] (2) The dispersion obtained by ultrasound was quickly injected into 20 mL of 1 M KOH, 50 μL at a time, until it was completely injected.

[0069] (3) The resulting mixed solution was sonicated for 1 h, and after the sonication was completed, it was washed, centrifuged, and dried to obtain a bifunctional catalyst based on iron phthalocyanine material, which was recorded as FePc.

[0070] Taking the FePc-LDH composite material in Example 1 as an example, Figure 1It can be seen from the TEM that the material presents a uniform composite lamellar structure with a lamellar size of about 100 to 200 nm.

[0071] The FePc-LDH prepared in Example 1 and the CoNi-LDH prepared in Comparative Example 1 were subjected to X-ray diffraction test. Figure 2 It can be seen that the prepared FePc-LDH and CoNi-LDH have a good correspondence with the cobalt and nickel hydroxides No.16-1896 and No.08-8940 in the PDF standard cards.

[0072] The prepared FePc-LDH in Example 1, CoNi-LDH in Comparative Example 1 and FePc in Comparative Example 2 were tested by Fourier transform infrared spectroscopy. Figure 3 As shown, 751cm -1 Peak representing Fe-N bonding, 1000-1450cm -1 The peaks representing organic functional groups can all reflect the material composite of FePc and CoNi-LDH.

[0073] Figure 4 The LSV curve OER diagram of the prepared FePc-LDH, CoNi-LDH and FePc in 1M KOH solution. In the OER test diagram, it was found that the sample FePc-LDH after the composite of iron phthalocyanine and cobalt nickel layered double metal hydroxide showed an improvement in synergistic catalytic performance, and the OER overpotential E 10 It is 270mV, which is the greatest performance advantage over commercial ruthenium oxide among the three groups of materials, indicating that the OER electrochemical performance of the composite material has been significantly improved.

[0074] Figure 5 The LSV curves of FePc-LDH, CoNi-LDH and FePc prepared in 0.1M KOH solution, saturated O2, and 1600rpm ORR graph. In the ORR test graph, it is found that the sample FePc-LDH after the composite of iron phthalocyanine and cobalt nickel layered double metal hydroxide shows the improvement of synergistic catalytic performance, and the ORR half-wave potential E 1 / 2 The FePc-LDH composite material also has the largest starting potential (0.91 V) and limiting diffusion current density (6 mA cm-2) among the three groups of materials. -2 ), indicating that the ORR electrochemical performance of the composite material has been significantly improved.

[0075] Figure 6The LSV curve OER diagram of the prepared FePc-LDH, FePc-LDH-2 and FePc-LDH-3 in 1M KOH solution. In the OER test diagram, it is found that the OER overpotential of the sample FePc-LDH after the composite of iron phthalocyanine and cobalt nickel layered double hydroxide gradually decreases with the increase of the amount of FePc introduced, indicating that the amount of FePc introduced has a certain promoting effect on the OER electrochemical performance of the composite material.

[0076] Figure 7 The LSV curves and ORR diagrams of the prepared FePc-LDH, FePc-LDH-2 and FePc-LDH-3 in 0.1M KOH solution, saturated O2, and 1600rpm. In the ORR test diagram, it was found that the ORR catalytic activity of the sample FePc-LDH after the composite of iron phthalocyanine and cobalt nickel layered double metal hydroxide did not change with the introduction amount of FePc, indicating that the introduction amount of FePc has no obvious effect on the ORR electrochemical performance of the composite material.

[0077] Figure 8 The LSV curve OER diagram of the prepared FePc-LDH, FePc-LDH-0.5h and FePc-LDH-6h in 1M KOH solution. In the OER test diagram, it was found that the OER catalytic activity of the sample FePc-LDH after the composite of iron phthalocyanine and cobalt nickel layered double hydroxide did not change significantly with the change of ultrasonic duration, indicating that the change of ultrasonic duration has no obvious effect on the OER electrochemical performance of the composite material.

[0078] Fig. 9 The LSV curves and ORR diagrams of the prepared FePc-LDH, FePc-LDH-0.5h and FePc-LDH-6h in 0.1M KOH solution, saturated O2, and 1600rpm. In the ORR test diagram, it was found that the ORR catalytic activity of the sample FePc-LDH after the composite of iron phthalocyanine and cobalt nickel layered double metal hydroxide changed significantly with the change of ultrasonic duration, showing a trend of first increasing and then decreasing. Comprehensive comparison of ultrasonic 1h is more ideal.

[0079] The above description is only a preferred embodiment of the present invention, which is only illustrative and not restrictive of the present invention. Those skilled in the art understand that many changes, modifications, and even equivalences may be made to the present invention within the spirit and scope defined by the claims of the present invention, but all of them will fall within the scope of protection of the present invention.

Claims

1. A method for preparing a bifunctional catalyst composited with iron phthalocyanine and cobalt nickel hydroxide layered materials, characterized in that: The following steps are involved: S1, uniformly dispersing cobalt salt and nickel salt in an organic solvent to obtain a dispersion; S2, slowly adding iron phthalocyanine powder to the dispersion in step S1, and ultrasonicating for 0.1 to 60 hours; S3, quickly injecting the dispersion obtained after ultrasonic treatment in step S2 into the strong alkaline solution, injecting 100 to 1000 μL each time until the dispersion is completely injected to obtain a mixed solution; S4, subjecting the mixed solution obtained in step S3 to ultrasonic treatment for 0.1 to 80 hours, washing, centrifuging and drying after the ultrasonic treatment to obtain a bifunctional catalyst composed of iron phthalocyanine and cobalt nickel hydroxide layered material, recorded as FePc-LDH.

2. The method for preparing a bifunctional catalyst of a composite of iron phthalocyanine and cobalt nickel hydroxide layered material as claimed in claim 1, characterized in that: In step S1, the cobalt salt is any one of cobalt chloride, cobalt nitrate, and cobalt sulfate, or a mixture of two or more thereof; the nickel salt is any one of nickel chloride, nickel nitrate, and nickel sulfate, or a mixture of two or more thereof; and the organic solvent is any one of methanol, ethanol, and N,N-dimethylformamide, or a mixture of two or more thereof.

3. The method for preparing a bifunctional catalyst composited with iron phthalocyanine and cobalt nickel hydroxide layered material as claimed in claim 1, characterized in that: In the step S1, the molar ratio of the cobalt salt to the nickel salt is 3:

2.

4. The method for preparing a bifunctional catalyst of a composite of iron phthalocyanine and cobalt nickel hydroxide layered material as claimed in claim 1, characterized in that: In the step S2, the dispersion amount of iron phthalocyanine is 2 to 200 mg / mL.

5. The method for preparing a bifunctional catalyst of a composite of iron phthalocyanine and cobalt nickel hydroxide layered material as claimed in claim 1, characterized in that: In step S3, the strong alkaline solution is any one of lithium hydroxide, sodium hydroxide, and potassium hydroxide, or a mixture of two or more thereof.

6. The method for preparing a bifunctional catalyst of a composite of iron phthalocyanine and cobalt nickel hydroxide layered material as claimed in claim 1, characterized in that: In step S3, the molar concentration of the strong alkaline solution is 0.1-10 mol / L.

7. The method for preparing a bifunctional catalyst of a composite of iron phthalocyanine and cobalt nickel hydroxide layered material as claimed in claim 1, characterized in that: In step S4, the solvent used for washing is any one of acetone, ethanol, and deionized water, or a mixture of two or more thereof.

8. The method for preparing a bifunctional catalyst of a composite of iron phthalocyanine and cobalt nickel hydroxide layered material as claimed in claim 1, characterized in that: In step S4, the drying is carried out by any one of ordinary air oven drying, vacuum drying, freeze drying or a mixture of two or more thereof, and the drying time is 1 to 144 hours.

9. A bifunctional catalyst composed of iron phthalocyanine and cobalt nickel hydroxide layered material prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the bifunctional catalyst of the composite of iron phthalocyanine and cobalt nickel hydroxide layered material as claimed in claim 9 in zinc-air batteries.

Citation Information

Patent Citations

  • Heterostructure iron / cobalt bimetallic phthalocyanine electrocatalyst and preparation method and application thereof

    CN111725529A

  • Metal sulfide composite difunctional electrocatalyst as well as preparation method and application thereof

    CN116895771A

  • Method for preparing Co-Fe-P composite electrode material for supercapacitor through electrodeposition method

    CN110223851A

  • Ultra-thin layered FeNi-LDH-FePc@MXene dual-functional catalyst and preparing method

    CN110404588A

  • Polymetal phthalocyanine-coated nitrogen-doped porous hollow carbon spheres as well as preparation method and application thereof

    CN116426970A